Optimalisasi Manajemen Stok dan Perencanaan Persediaan Seragam Sekolah pada Toko Empat Bersaudara - Rina Susanti; Engla Desnim Silvia; Fatma Ariani (ARDHI : Jurnal Pengabdian Dalam Negri, 2026)
The purpose of this community service activity is to optimize stock management and inventory planning for school uniforms at Toko Empat Bersaudara as an effort to overcome unstructured stock recording, difficulties in controlling product variations, and the risk of overstocking or stock shortages during peak demand periods. The methodology used was a descriptive-qualitative partnership-based approach through observation, discussion, socialization, simulation, mentoring, and formative and summative evaluation. The results show that the partner gained a better understanding of the importance of recording incoming goods, outgoing goods, stock balances, product codes, minimum stock levels, and reorder forms. In addition, this activity produced simple stock management tools, including stock books, spreadsheet templates, recording guidelines, product code labels, and order forms that can be implemented gradually. The implication is that simple stock recording systems can help retail MSMEs improve operational efficiency, accelerate customer service, and support inventory decisions based on historical data.